A Review of Managing Water Resources in Malaysia with Big Data Approaches - Cheah, Ryan Wei Jie; Tan, Cha Yao; Teo, Fang Yenn; Goh, Boon Hoe; Mah, Yau Seng (Emerald Publishing, 2021)
Big data have rapidly developed as a viable solution to many problems faced in engineering industries. Specifically, in the industry of water resource engineering, where there is a tremendous amount of data, various big data techniques could be applied to achieve innovative and efficient solutions for the industry. This study reviewed the proposal of big data as potential approaches to solve various difficulties encountered in managing water resources and related applications in Malaysia. The advantages and disadvantages of big data applications have also been discussed along with a brief literature review and some examples of case studies